Political Families: Narration, Memory and Healing in Cristina García’s Dreaming in Cuban - Kovács, Ágnes Zsófia (Acta Hispanica, 2020)
The paper interprets Cristina García’s novel Dreaming in Cuban against the backdrop of contemporary multicultural identity prose by women. Against expectations about the possibility of healing and belonging in the feminine diasporic text, the novel problematizes the possibility and costs of healing, reconnecting, and reconciliation. The text represents how profoundly political and family history are interconnected on an individual level, and how the intersection of family, politics, and individual limits the scope of change for the protagonist.